Kinetics of plasma viremia and soluble nonstructural protein 1 concentrations in dengue: differential effects according to serotype and immune status. - Duyen, H; Ngoc, T; Ha, D; Hang, V; Kieu, N; Young, P; Farrar, J; Simmons, C; Wolbers, M; Wills, B (2011)
We describe the magnitude and kinetics of plasma viremia and nonstructural protein 1 (sNS1) levels in sequential samples from 167 children with acute dengue, enrolled early in a community study in Vietnam. All children recovered fully, and only 5 required hospitalization. Among those with dengue virus type 1 (DENV-1), plasma viremia was significantly greater in primary (49) than secondary (44) infections and took longer to resolve. In primary DENV-2 and 3 infections, viremia was significantly lower than among primary DENV-1 infections. Concentrations of sNS1 were significantly higher for DENV-1 than for DENV-2 after adjusting for viremia, with marked differences in the kinetic profiles between primary and secondary infections. Secondary infection and higher viremia were independent predictors of more severe thrombocytopenia, and higher viremia was associated with a small increase in hemoconcentration. Our findings identify clear serotype and immune-status related effects on the dynamics of dengue viremia and sNS1 responses, together with associations with important clinical parameters.